Estimates of true ileal digestibilities of corn, soybean meal and alternative feed ingredients for swines - Bellaver, Claudio; A. Easter, Robert (Pesquisa Agropecuaria Brasileira, 1998)
Nine crossbred barrows with an initial weight of 52.59±.57 kg were each surgically fitted with a T-cannula at the terminal ileum in order to measure the coefficients of true amino acid digestibilities (TAAD) of eight feedstuffs for subsequent use in testing the utility of amino acid digestibility values in diet formulation. The feed ingredients investigated were: corn, wheat bran (WB), two sources of soybean meal (SBM 1 and SBM 2), cottonseed meal (CSM), poultry by-product (PBP), and meat and bone meal (MBM 1 and MBM 2) from two origins. A nitrogen free diet (NFD) was used to estimate the endogenous losses of amino acids. The TAAD coefficients in corn and WB were significantly lower (P≤.01) than in the other sources except for lysine in CSM and threonine in MBM 1. True lysine digestibility coefficients for corn (59.9%) was in the range of values found in the literature. The SBM 1 and SBM 2 yielded similar (P≥.01) amino acid digestibility. The MBM 1 and MBM 2 despite visual differences in appearance were also similar (P≥.01). The obtained estimates are in the range of literature values and can be used to calculate diets based on the amino acid digestibility.